ANALISIS DAN VISUALISASI DATAPENDERITA PENYAKIT DBD DI SITUBONDO MENGGUNAKAN PLATFORM TABLEAU - Basmalah Abirestu Maulisuriandhy; M. Syauqi Haris; Ahsanun naseh Khudori (Yayasan Nusantara Hasana Berdikari, 2024)
Cases of dengue fever in Situbondo are very fluctuating and unpredictable. This shows that dengue fever is still a problem that requires serious health attention. The infectious disease dengue fever is caused by the bite of the Aedes aegypti mosquito. Fluctuations in dengue fever cases are due to erratic rainfall. Sometimes rainfall is higher and the rainy season is longer. On the other hand, sometimes rainfall is relatively lower and the dry season is longer. This research aims to analyze and visualize data on dengue fever sufferers in Situbondo using the Tableau platform. The data used is map data per region or spatial data that has geographical references and historical data on dengue fever patients in Situbondo from 2016 to 2022. Data was obtained from the website Tanahair.indonesia.go.id and the Situbondo Community Health Center. The research results show that data visualization using Tableau can produce good, effective, interesting and efficient information. The results of data visualization of dengue fever sufferers in Situbondo showed that there were 2 cases of death. Cases of dengue fever sufferers are spread throughout all villages in Situbondo. It is hoped that the results of this research can help in adopting appropriate policies to control dengue fever in Situbondo.